MENELAAH SIGNIFIKANSI PENERAPAN BIAYA RELEVAN DALAM PENGAMBILAN KEPUTUSAN BRANDING BISNIS SPA - Salmah, Salmah; Halpiah, Halpiah; Putra, Hery Astika (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
Purpose: This study aims to determine the management team's understanding of relevant costs, how to determine relevant costs in branding decision making and to determine whether branding cost decisions can increase Matcha Natural SPA's business profits), Methods: This type of research is qualitative research with a case study research approach. The main informants in this study were the owner of Matcha Natural SPA, manager, and accounting department, supporting informants were 4 employees and 4 customers, Analysis data: Data analysis used in this study is qualitative data analysis carried out in several stages, namely case analysis, content analysis, inductive analysis and analysis based on logic, Result and discussions: The results of the study indicate that Matcha Natural SPA management has implemented relevant costs well even though it has not been maximized, this can be seen from the use of balanced products in profit acquisition, although in theory the management team does not yet understand properly what relevant costs are, but has been able to increase profits significantly by 7.69%, Conclusion: Matcha Natural SPA has implemented relevant costs well even though it has not been maximized in making branding decisions as evidenced by the application of relevant costs in making branding decisions, customers feel satisfied and customers are increasingly enthusiastic about reserving and enjoying the SPA services offered, in addition, relevant costs for branding decisions slowly provide an increase in business profits. In the future, it is hoped that Matcha Natural SPA will be able to compile relevant costs, especially those related to branding decision-making, so that all costs that have been incurred can be traced and the significance of the returns in the form of monthly income or annual profit can be compared.